Independence of Brushing Teeth to Free-Plaque Score in Preschool Children: A Cross Sectional Study - Ngatemi; Tedi Purnama; Ni Nyoman Kasihani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Preschool children do not yet have independence in maintaining oral hygiene, especially brushing teeth. Bad oral hygiene causes plaque accumulation, where brushing teeth is a simple act of removing plaque and food debris with a toothbrush and toothpaste, because plaque and food debris are the main causes of dental caries. Purpose: This study was to determine the relationship between independence of brushing teeth to free plaque score in preschool children. Method: This type of analytic observational study with cross sectional design. The research was conducted on the students of Bintang Kindergarten in Pondok Labu Village, Cilandak District, South Jakarta. Data collection using the observation sheet brushing teeth and index free plaqu score.Data analysis using Chi-Square. Result: Less of independence in brushing teeth as many as 28 respondents (87.5%) and as many as 4 respondents (12.5%) independently brushed their teeth while the free plaque score with good criteria was 3 respondents (9.4%) and 29 respondents (90.6%) with bad criteria. Independence of brushing teeth on the free plaque score showed that the p-value was 0.001 (p <0.05). Conclusion: There is a significant relationship between independence of brushing teeth on free plaque score in preschool children.